Symbolizing, signifying and marking through gathering: gender strategies to face the forest industry in Nahuelbuta (Chile) - Giménez Delgado, Inés (Filanderas, 2017)
Plantations of pine and eucalyptus occupy more than 60% of the land area of the Lower Border of Nahuelbuta, coastal territory in south-central Chile. This is perceived by some Mapuche and peasant sectors as a mechanism of dispossession, which is preceded by historical agrarian, ethnic and environmental struggles. To contest the ecological and water crisis and the destructions of local living economies caused by this industrial monoculture model, some women's associations are developing territorialization strategies. They are based in the generation of social economy networks, the recovery of traditional and local knowledge around wild fruits, the restoration of reciprocity practices and the defense of the fundamental rights. These local strategies led by rural women are enrolled in a complex global arena where many social actors dispute the appropriation of social imaginaries and the use of common goods.
Keywords: Forest Industry; Agroecology; Common Goods; Non-Wood Forestry Products (NWFP); Territorialization